An Analysis of Intermediate Level Speaking Students’ Perception of Cake Application for Speaking Skill Improvement - Ridhallah, Rizky; Yoestara, Marisa; Faudi, Faudi (Universitas Teuku Umar, 2024)
This study aimed to explore students' perception of the Cake application's effectiveness in enhancing their speaking skills. Using a descriptive qualitative method, the researcher surveyed 14 students from Serambi Mekkah University's English Education program. A structured questionnaire with 20 questions gathered data on the participants' experiences and improvements resulting from using Cake. The analysis revealed that 93.69% of intermediate-level students believed Cake significantly improved their speaking skills. These findings establish Cake as a valuable Mobile-Assisted Language Learning tool for intermediate-level students, fostering confidence and fluency in spoken English. The study's implications highlight the importance of incorporating technology-enhanced language learning tools like Cake into educational programs. Educators and curriculum developers can benefit from these insights when designing language learning strategies. In conclusion, this research confirms the positive perception of students towards Cake's impact on speaking skills. The study supports the effectiveness of Mobile-Assisted Language Learning tools like Cake in enhancing language proficiency among intermediate-level students. Further research in this area can contribute to the advancement of language learning methodologies.